Problem-based Learning and Pedagogies of Play - Marietjie Havenga; Jako Olivier; Byron J Bunt; Amane Oueriagli; Amit Dhakulkar; Aubrey Golightly; Azeddine Benelrhali; Carolina Botha; Chanene Nordgaard; Charlene du Toit-Brits; Daniel Burgos; Elma Marais; et al. (AOSIS Books, 2023)
The focus of this book is original research regarding the implementation of problem-based learning and pedagogies of play as active approaches to foster self-directed learning. With the Fourth Industrial Revolution (4IR) in mind, educational institutions need to rethink teaching and learning for the future. As such, active engagement can be encouraged, as evident in this book, where problem-based learning drives learning through real-world problems, while pedagogy of play focuses on innovative environments where the action of play and learning are integrated with the aim of developing SDL. The following are addressed in the chapters: an overview of problem-based learning and pedagogy of play, metaliteracy, playful problem-based learning tasks, computational thinking in game-based tasks and geometry, solving puzzles, applying LEGO®, using drama as the pedagogy of play and implementing educational robotics. The empirical research findings disseminated in this book aim to inspire academics in the research focus area of self-directed learning with active learning approaches in the school and tertiary classroom that hold affordances to enhance 21st-century skills. Active learning is an umbrella term for pedagogies that mainstream student engagement, such as problem-based learning, cooperative learning, gamification, role-play and drama. This scholarly book highlights various engaging pedagogies.